Smong: Kearifan Lokal Sebagai Bentuk Warisan Budaya Mitigasi Bencana Masyarakat Simeulue, Nanggroe Aceh Darussalam - Ambar Teguh Sulistiyani; Miladiyatu Tsania Zulfa (Universitas Serang Raya, 2023)
Indonesia is often hit by disasters but disaster management has not been optimal. The focus of disaster management is only on post-disaster. Meanwhile, a post-disaster management approach alone will not be able to control the impact of a disaster early. This paper aims to analyze improvements in disaster mitigation for responsiveness in dealing with disasters both pre, during and post-disaster using local wisdom in the form of the